DESIGN AND FABRICATION OF A RACING KART FOR BOSCH POWER TOOLS ASIA CORDLESS RACE 2011 (CHASSIS FRAME AND STEERING SYSTEM) - ABDUL RAZAK, MUHAMMAD RIDHWAN (2011)
BOSCH POWER TOOLS ASIA CORDLESS RACE 2011 IS A COMPETITION THAT CHALLENGES LOCAL UNIVERSITY STUDENT FROM CHINA, THAILAND, PHILIPHINES, SOUTH KOREA AND MALAYSIA TO DESING A RACING KART POWERED ENTIRELY 4 BOSCH GSB 18V-Li PROFESSIONAL CORDLESS DRILL.THE OBJECTIVE OF THE PROJECT IS TO DESIGN, ANALYZE AND FABRICATE A PROPER CHASSIS FRAME AND STEERING SYSTEM FOR A RACING KART THAT IS LIGHTWEIGHT, LOW COST, FUNCTIONAL AND DURABLE.